(untitled) (International Journal of Physiotherapy, 2016)
Background: More than 77% of stroke survivors have upper limb dysfunction. The scientific evidence for interventions in upper limb rehabilitation in stroke has shown variable results. To improve health care treatments in this domain it is needed to know what modalities are actually being used by physiotherapists. Methods: A national web-based survey focused in characterizing the profile of Portuguese physiotherapists working in post-stroke upper limb rehabilitation was conducted in 237 health institutions (n= 462 physiotherapists). The recruitment was conducted from August to December 2014. Analytic and descriptive analysis were used. Results: A total of 179 physiotherapists from 64 different locations from Portugal answered the survey, with a rate of response of 38.7%. The average age of respondents was 29.25±6.4 years old and predominantly finished the graduation or bachelor degree between 2001 and 2010. More than half hadn´t carried out any specialization in neurologic rehabilitation area. The top 5 modalities most used in the rehabilitation of upper limb in acute stroke are Goal Oriented Tasks (93.4% n=141), Motor Learning (89.4% n=135), Passive Mobilization (88.7% n=134), Task Repetition (87.4% n=132) and Bobath/Neurodevelopmental Therapy (86.9% n=131). Conclusions: The main modalities used for physiotherapists in upper limb rehabilitation in acute stroke have sparse levels of evidence. It is important to alert teachers, formers, physiotherapists and students for interventions with supported scientific results.